Attenuation of skin injury by a MARCO targeting PLGA nanoparticle - Ummiye V. Onay; Dan Xu; Dauren Biyashev; Spencer T. Evans; Michael M. Demczuk; Tobias Neef; Joseph R. Podojil; Sara Beddow; Nathan C. Gianneschi; I. Caroline Le Poole; Stephen D. Miller; Kurt Q. Lu (npj Regenerative Medicine)
Abstract Cutaneous exposure to the DNA alkylating class of chemotherapeutic agents including nitrogen mustard (NM) leads to both skin injury and systemic inflammation. Circulating myeloid subsets recruited to the skin act to further exacerbate local tissue damage while interfering with the wound healing process. We demonstrate herein that intravenous delivery of poly(lactic-co-glycolic acid) immune-modifying nanoparticles (PLGA-IMPs) shortly after NM exposure restricts accumulation of macrophages and inflammatory monocytes at the injury site, resulting in attenuated skin pathology. Furthermore, PLGA-IMPs induce an early influx and local enrichment of Foxp3+ regulatory T cells (Treg) in the skin lesions critical for the suppression of myeloid cell-pro-inflammatory responses via induction of IL-10 and TGF-β in the cutaneous milieu. Functional depletion of CD4+ Tregs ablates the efficacy of PLGA-IMPs accompanied by a loss of local accumulation of anti-inflammatory cytokines essential for wound healing. Thus, in severe skin trauma, PLGA-IMPs may have therapeutic potential via modulation of inflammatory myeloid cells and regulatory T lymphocytes.